Anti-Mycobacterium tuberculosis activity of antituberculosis drugs and amoxicillin/clavulanate combination - Furlan Pagliotto, Aline Daniele; Caleffi-Ferracioli, Katiany Rizzieri; Lopes, Mariana Aparecida; Baldin, Vanessa Pietrowski; Fujimura Leite, Clarice Queico [UNESP]; Pavan, Fernando Rogerio [UNESP]; Lima Scodro, Regiane Bertin de; Dias Siqueira, Vera Lucia; Cardoso, Rosilene Fressatti (Elsevier B.V., 2016)
We report the in vitro drugs interaction by the resazurin drugs combination micro-titer assay (REDCA) of amoxicillin (AMO)/clavulanate (CLAV) with isoniazid (INH), ethambutol (EMB), and rifampicin (RIF) against susceptible and resistant Mycobacterium tuberculosis isolates. The addition of AMO/CLAV to classical antituberculosis drugs should be explored as a promising alternative for the treatment of resistant tuberculosis (TB). Copyright (C) 2015, Taiwan Society of Microbiology. Published by Elsevier Taiwan LLC.
Keywords: amoxicillin/clavulanate; checkerboard; Mycobacterium tuberculosis; synergism; tuberculosis